2021
DOI: 10.3389/fpls.2021.679063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Flower Volatile Diversity in Natural Populations of Origanum vulgare subsp. hirtum (Link) Ietsw. in Bulgaria: Toward the Development of a Core Collection

Abstract: We studied the genetic and flower volatile diversity in natural populations of Origanum vulgare subsp. hirtum (Link) Ietsw. in Bulgaria using simple sequence repeat (SSR) and sequence-related amplified polymorphism (SRAP) markers and gas chromatography/mass spectrometry (GC/MS) analysis of flower volatiles from individual plants. Two regions, including the Kresna Gorge and Eastern Rhodopes, typical for the species comprising eight populations and 239 individual plants were included in this study. An analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The SRAP approach, developed by Li and Quiros [ 21 ], is a simple, effective, and reliable marker system that can be adapted for a variety of purposes. The SRAP markers have been successfully applied for analysis of genetic diversity in plant genetic resources and natural populations from the Lamiaceae family [ 22 , 23 ]. Alekseeva et al [ 23 ] studied genetic diversity in Origanum vulgare subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SRAP approach, developed by Li and Quiros [ 21 ], is a simple, effective, and reliable marker system that can be adapted for a variety of purposes. The SRAP markers have been successfully applied for analysis of genetic diversity in plant genetic resources and natural populations from the Lamiaceae family [ 22 , 23 ]. Alekseeva et al [ 23 ] studied genetic diversity in Origanum vulgare subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The SRAP markers have been successfully applied for analysis of genetic diversity in plant genetic resources and natural populations from the Lamiaceae family [ 22 , 23 ]. Alekseeva et al [ 23 ] studied genetic diversity in Origanum vulgare subsp. hirtum and reported that the SRAP assay is sensitive in the detection of heterogeneity between individuals within populations of the same species.…”
Section: Resultsmentioning
confidence: 99%
“…All OEO compounds were visualized using a heatmap ( Figure 1 A). According to the plant materials and the composition analysis results, habitats may have specific effects on OEO composition, in addition to various species, artificial cultivation, and selection factors [ 2 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natural plant extracts, such as essential oils and organic acids, have a specific antibacterial effect [ 1 ]. Essential oil exerts a bacteriostatic effect on multiple targets in bacteria by disrupting the bacterial membrane and reducing the intracellular ATP concentration and intracellular pH value [ 2 , 3 ]; thus, developing antibiotic resistance is not easy. In addition, essential oil has been extensively studied for applications in food, hygiene, cosmetics, and medicine for its antibacterial properties [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AMOVA revealed that the variation among E. stauntonii populations (18.53%) was higher than that of many other plant species, such as Origanum vulgare subsp. hirtum (8%) ( Alekseeva et al, 2021 ) and Allium sativum L. (12.29%) ( Poljuha et al, 2021 ), suggesting that disruption of gene flow between the populations played a role in determining the genetic differentiation of populations. Similarly, the results of the Mantel test ( r = 0.56, p < 0.001) showed that increase in geographic distance reduced gene flow.…”
Section: Discussionmentioning
confidence: 99%